Three-dimensional transport of coral larvae and associated population connectivity in the coastal area of Okinawa Island, Japan - Zhang Tianrui; Uchiyama Yusuke; Takeyasu Kimika (E3S Web of Conferences)
In recent years, global warming has intensified coral bleaching worldwide. The mesophotic zone (MPZ) at depths of 30-150 meters, where photosynthesis is viable and water temperatures are stable, is expected to serve as a refuge and gene resupply source for shallow-water corals. This study quantitatively evaluates the 3D population connectivity between shallow-water corals and MPZ corals in the potential coral habitats surrounding Okinawa Island. Utilizing a triple-nested high-resolution 3D ocean circulation model, an offline, 3D Lagrangian advection-dispersion model for planktonic coral larvae was developed. Results show that 3D intra-island coral connectivity is strongly influenced by topographically constrained residual currents around the island. Coral larvae released from shallow areas are transported in a clockwise direction around the island. While the larvae released from the west coast are transported to the east coast by crossing the northern tip of the island, their movement is significantly hindered at the southern tip by a shallow channel as a topographic barrier. Conversely, this clockwise transport is much less pronounced in the MPZ, resulting in lower connectivity between the west and east coasts. In addition, potential source areas of coral larvae were analyzed to determine an island-wide coral network that could support coral conservation efforts in Okinawa.